Investigating influenza virus A pleomorphy - DEE, KIERAN (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2019)
Clinical isolates of influenza A virus particles display a pleomorphic phenotype, where particles can range in size from 100 nm to 10 ?m in length while maintaining uniform diameters. Conversely, most laboratory-adapted strains that have undergone serial passage in laboratory substrates display a solely spherical particle phenotype. We were interested to investigate the biological significance of filamentous particles. Isogenic viruses of the strain A/Victoria/3/1975 were generated. The wild type (WT) virus, Vic75 WT, generated filamentous particles, a mutant that expressed a different M segment,Vic:PR8M, produced solely spherical viral particles from infected cells. A spherical morphology correlated with increased replication capacity in immortalised cells and the increased growth capacity could be attributed to residue 41 of the M1 protein. We demonstrate that filamentous virus particles are more resistant to inhibition by polyclonal anti-sera directed against the receptor binding protein. We also demonstrate that filamentous particles are more resistant to inhibition by respiratory mucus, and this is dependent on viral neuraminidase activity. We report that the morphologies of cell-associated and released viral particles generated from MDCK cells do not match the cell-associated and released morphologies of particles generated from infected primary respiratory epithelial cells. We also demonstrate that Vic75 WT virus particles are more stable in aerosolised droplets, and this is dependent on the composition of the buffer in which viruses are diluted. Finally, we demonstrate that compared to Vic:PR8M, Vic75 WT viruses are more stable at 37oC and at lower pHs viruses and this is independent of virion morphology.
APPROVED
Keywords: Morphology; Influenza